[PP.28.20] DAPAGLIFLOZIN ACUTELY REDUCES AORTIC STIFFNESS, RESTORES ENDOTHELIAL DYSFUNCTION AND INDUCES RENAL VASODILATION IN TYPE 2 DIABETIC PATIENTS: A PILOT STUDY. (September 2017) - Bruno, R.M.; Ghiadoni, L.; Giannini, L.; Vitolo, E.; Seghieri, M.; Taddei, S.; Solini, A.
Abstract : Objective: Sodium-glucose co-transporter-2 (SGLT2) inhibitors are a novel drug class, able to reduce blood pressure (BP) values and cardiovascular events in type 2 diabetes (T2DM), Though BP and glucose control certainly contribute to the cardiovascular protection mediated by SGLT2-inhibitors, other mechanisms are plausible and not fully elucidated. Aim of this study is to investigate whether dapagliflozin is able to acutely modify systemic and renal vascular function in T2DM. Design and method: 16 T2DM patients, treatment-naïve for BP (age 57 ± 9 years, 11 men, BMI 30.5 ± 6.7, HbA1c 56.0 ± 6.8 mmol/mol) were enrolled. Neuro-hormonal and vascular variables were assessed before (V0) and after (V1) a 2-day treatment with dapagliflozin 10 mg/die per os. 24h-urinary sodium and glucose, diuresis and free-water clearance were measured at V0 and V1. Brachial artery endothelium-dependent and independent vasodilation were assessed by flow-mediated dilation (FMD) and automated image analysis. Pulse wave velocity (PWV), central BP and its augmentation were assessed by applanation tonometry. Renal resistive index (RI) was assessed and renal vasodilating capacity evaluated by administration of low-dose glyceril trinitrate (GTN). Results: 2-day treatment with dapagliflozin induced a significant decrease in brachial systolic BP (130.7 ± 12.8 to 125.4 ± 11.2 mmHg, p < 0.05), an increase in 24h-diuresis (1400[750] to 2000[750] ml, p < 0.05), 24h-urinary glucose (406[3465] to 66239[43780] mg/24 h, p < 0.05), while natriuresis and fasting blood glucose were unchanged. FMD was significantly increased (2.8 ± 2.2 to 4.0 ± 2.1%, p < 0.05), in the presence of unchanged brachial artery diameter, shear rate and response to GTN. PWV was reduced (10.1 ± 1.6 to 8.9 ± 1.6 m/s, p < 0.05); a trend persisted even after correction for mean BP (p = 0.053). RI was reduced (0.62 ± 0.04 to 0.59 ± 0.05, p < 0.05), while RI response to GTN was unmodified. Changes in FMD, PWV and RI were not associated with changes in BP. Conclusions: 2-day treatment with dapagliflozin induce a significant improvement in systemic endothelial function, arterial stiffness and renal vasodilation; this effect is independent of changes in BP and occurrs in the presence of stable blood glucose and natriuresis. These preliminary data suggest that dapagliflozin has a direct beneficial effect on the vasculature, which might translate in reduced cardiovascular risk.